Postharvest pathogens and disease management - Narayanasamy, P (John Wiley & Son, 2006)
The book tells about the principles and methods of avoiding and managing posthavest diseases of fruits and vegetable products in an afficient, economical and environmentally feasible manner, allowing producers to sell safer, higher-quality produce to the public and prevent the losses associated with posthavest disease